2018
DOI: 10.1016/j.ijsu.2018.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Conversion is a risk factor for postoperative anastomotic leak in rectal cancer patients - A retrospective cohort study

Abstract: Conversion during laparoscopic LAR was found to be associated with an increased risk for the postoperative AL in RC patients. A nomogram model incorporating conversion, gender and patient's clinical N stage seems to offers a useful tool for predicting postoperative AL in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
6
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
6
6
3
1
Order By: Relevance
“…It was a hint for surgeons that a temporary stoma could reduce the incidence of reoperation necessitated by AL. Besides, the stoma rate was 66.2% in our study which was higher than several other studies (12,20,25). In contrast, in our study the average distance of tumor from the anal verge was lower than that in most previous studies (around 7.5 cm) (12,20,25,26).…”
contrasting
confidence: 85%
See 2 more Smart Citations
“…It was a hint for surgeons that a temporary stoma could reduce the incidence of reoperation necessitated by AL. Besides, the stoma rate was 66.2% in our study which was higher than several other studies (12,20,25). In contrast, in our study the average distance of tumor from the anal verge was lower than that in most previous studies (around 7.5 cm) (12,20,25,26).…”
contrasting
confidence: 85%
“…Besides, the stoma rate was 66.2% in our study which was higher than several other studies (12,20,25). In contrast, in our study the average distance of tumor from the anal verge was lower than that in most previous studies (around 7.5 cm) (12,20,25,26). In our study, the overall average distance was 6.99±3.18 cm, and that in the stoma group was 5.75±2.52 cm, while in non-stoma group that was 9.41±2.90 cm, which implied that there were more low rectal cancer patients in our study.…”
contrasting
confidence: 78%
See 1 more Smart Citation
“…The nomogram decision curve analysis is shown in Figure 2. The calibration curve of the nomogram for the probability of mortality demonstrated good agreement between prediction and observation in the primary cohort (Figure 2) (24). The decision curve showed that if the threshold probability of a patient or doctor is >0%, using the nomogram to predict the mortality for COVID-19 patients adds more benefit.…”
Section: Development and Validation Of A Nomogrammentioning
confidence: 80%
“…Eindeutig führen Konversionen zu einer Verlängerung der Rekonvaleszenz. Es gibt aber auch eine Reihe von Hinweisen darauf, dass Konversionen bei laparoskopischen Operationen des Rektumkarzinoms mit einer Erhöhung der Anastomoseninsuffizienzrate [13,14] und mit einer Verschlechterung des tumorfreien und Gesamtüberlebens einhergehen [13]. Daher ist zu betonen, dass sich in den vorliegenden vergleichenden Untersuchungs-serien für die TaTME eine kumulative Konversionsrate von unter 1 % findet, während in den laparoskopischen Armen Konversionsraten von etwa 10 % beschrieben sind (.…”
Section: In Vielen Studien Zur Minimalinvasiven Tme Finden Sich Hohe unclassified